Perlindungan Hukum terhadap Rekening Nasabah yang Otomatis Berstatus Dormant pada Sistem Perbankan (International Forum of Researchers and Lecturers, 2025)
Dormant status on a bank account is a condition in which an account is declared inactive because there have been no transactions for a certain period of time, so that it is automatically frozen by the bank. In Indonesian banking practices, changes in account status to dormant are often carried out based on the bank's internal policy without any clear notification to customers. This raises legal issues, especially related to the protection of customer rights to their funds, transparency of information, and access to financial services. The purpose of this study is to examine the extent to which the State provides legal protection that will be received by customers against the policy of automatically changing account status to dormant, as well as to evaluate the regulations in the Indonesian banking legal system. This study uses a normative legal approach, namely an approach that is based on literature studies by examining positive law, legal doctrine, and relevant literature. The approaches used include the statute approach and the conceptual approach. The results of the study indicate that legal protection for customers with dormant account status is still weak because there are no specific regulations that explicitly regulate this matter. The applicable legal regulations are still inclusive or general and do not sufficiently guarantee legal certainty and justice for customers. Therefore, special regulations are needed from the Financial Services Authority (OJK) and Bank Indonesia that establish transparent mechanisms, easy procedures, and balanced protection of customer rights. It is hoped that strengthening these regulations can increase public trust in the banking system and guarantee justice and legal certainty.